Testing the effectiveness and cost-efficiency of livestock guarding dogs in Botswana - Horgan, Jane Elizabeth (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2016)
Livestock guarding dogs (LSGDs) have been used for centuries to reduce depredation on livestock and more recently, to facilitate the conservation of threatened predator species. Conservation NGOs (non-government organisations) in southern Africa promote the use of Anatolian Shepherds as LSGDs. However, livestock farmers in Botswana have been using a variety of different breeds for this purpose, including the local mixed-breed "Tswana" dogs. Postal, telephonic and face-to-face interview questionnaires were administered to 108 livestock farmers in Botswana to gauge how their LSGDs were being used, in order to determine what factors contributed to the success and affordability of these dogs. Eighty-three percent of farmers had LSGDs which equaled or decreased livestock depredations on their farms, with an average reduction in livestock depredation of 75% per year. This equated to an average saving of US$2,017 annually per farm. The costs of purchasing (average US$27) and maintaining the 198 LSGDs in my study (average US$169/LSGD/year) were very low compared to other countries and helped contribute to the high profits obtained by farmers (average US$1,497/farm or US$789/LSGD). A unique investigation of different breeds was possible due to the diverse array of breeds in the sample (Anatolian Shepherds, Cross Breeds, Tswana dogs, Greyhounds and Pitbulls), with the crossbreed dogs (Crosses and Tswana LSGDs) performing the best. LSGDs that reduced depredation and had minimal behavioural problems were the most likely to incite positive changes in their owners in regards to attitudes towards predators. Sixtysix percent of farmers stated that they were more tolerant of predators since obtaining a LSGD, and 51% reported that they were less likely to kill predators since obtaining a LSGD. My results indicate that successful, well-behaved LSGDs are a cost-effective tool that has the ability to increase farm productivity and improve predator-farmer conflicts in Botswana. The methods recommended in my thesis, in particular the benefits of using local breeds of dog as LSGDs, can be implemented on farming practices the world over to assist farming productivity and to promote conservation efforts.
Keywords: Uncatalogued